QUADRICEP TENDON TURNDOWNS FOR MPFL RECONSTRUCTION: AN ANATOMICAL DIFFERENCE BETWEEN THE ORIGINS OF THE QUADRICEP TENDON AND MPFL ON THE PATELLA. Issue 3 (31st March 2019) - Rustad, Audrey; Anchustegui, Nicolas G.; Troyer, Stockton; Shea, Cooper; Dingel, Aleksei; Ganley, Theodore J.; Shea, Kevin
Background: Quadriceps tendon (QT) turndowns are an alternative method for medial patellofemoral ligament (MPFL) reconstruction, with several distinct advantages: 1. Avoids the use of patella bone tunnels, which have been associated with patella fracture, 2. Avoids the use of separate incision for hamstring tendon harvest, and 3. Avoids the use of allograft tissue, which adds a significant cost. The disadvantage of the Quad Tendon graft is that the most distal reflection point on the patella may not duplicate the patella origin of the native MPFL. The purpose of this study was to determine whether a QT graft for MPFL reconstruction is anatomically analogous to the native MPFL origin in a skeletally immature population. Methods: Three skeletally immature cadaveric knee specimens (ages 10 and 11, 11) were dissected to reveal the MPFL and QT origins on the patella. The proximal and distal extent of the MPFL was marked on the medial border of the patella. The medial aspect of the quad tendon was reflected as far as possible in both a medial and distal position on the patella, to function as the MPFL graft. The distance was measured between the midpoint of the patellar origin of the MPFL in the coronal plane, and the most distal aspect of the patellar origin of the reflected quad tendon. Results: In the 10, 11, and 11 year-old specimens, the distance between the midpoint of MPFL patellar origin and the QT patellar origin was 3.4 cm, 4.3, and 3.7 mm. In all cases, the QT reflected origin was at least 7 mm anterior to the to native MPFL origin on the medial border of the patella. Conclusion: A disparity exists between the patellar origin of the MPFL and the patellar origin of the quad tendon, with the patellar origin of the MPFL being more medial, more distal, and more posterior than the reflected patellar origin of the QT graft. Surgeons performing MPFL reconstructions may find this anatomically valuable as they attempt to duplicate the normal anatomy of the patella stabilizers during surgical reconstruction. While the QT remains a good graft choice for MPFL reconstruction, attachment of the QT graft at the native origin of the MPFL may better reproduce the anatomy of the MPFL. Figures: Figure 1:. Sagittal view of the 3mm lateral drill tunnels. Figure 2:. Sagittal view of the 3mm medial drill tunnels.